Padre Pio under investigation : the secret Vatican files - Castelli, Francesco, 1981-; Bockhorn, Giulietta; Bockhorn, Lee; Messori, Vittorio, 1941- (San Francisco : Ignatius Press, 2011)
De heilige Padre Pio vertoonde stigmata, en het Vaticaan voert zeker in dergelijk geval een heel grondig onderzoek uit alvorens over te gaan tot zaligverklaring en heiligverklaring.
Every aspect of Padre Pio's life is revealed in documents that include his depositions and letters from his spiritual father and a chronology of his life.
Originally published in Italian as: Padre Pio sotto inchiesta : l'"autobiografia" segreta. Milano : Edizioni Ares, c2008.
Includes bibliographical references and index.
Keywords: Pio, -- of Pietrelcina, Saint, -- 1887-1968.; Catholic Church -- Clergy -- Biography; Stigmatization -- Case studies